Konsep diri dan kecemasan komunikasi interpersonal pada mahasiswa - Asti Puspitasari Gaspersz (INNER: Journal of Psychological Research, 2022)
The purpose of this study was to determine the relationship between self-concept and communication anxiety in students. Participants in this study were 150 students of the Faculty of Teacher Training and Education, Pattimura University, Ambon, which were taken incidentally. The data collection method used a self-concept and interpersonal anxiety scale which was compiled by the research itself. Based on the results of data analysis using the Spearman's Rho Correlation, a score of rxy = 0.354 with a significance of p = 0.000 (p <0.001) which means that there is a significant positive relationship between self-concept and interpersonal anxiety in students. The results of this study are not in line with the hypothesis that was built. The limitations of the study are further discussed. Keywords : Self-Concept, Interpersonal Communication Anxiety